1997
DOI: 10.1200/jco.1997.15.5.2056
|View full text |Cite
|
Sign up to set email alerts
|

Poorly differentiated carcinoma and poorly differentiated adenocarcinoma of unknown origin: favorable subsets of patients with unknown-primary carcinoma?

Abstract: The long median survival and chemotherapy responsiveness of UPC patients with PDC and PDA could not be confirmed. However, subpopulations with prolonged median survival durations could be defined, and the value of chemotherapy in this group remains to be determined. Identification and exclusion of treatable or slow-growing malignancies may account for the poor survival of the PDC and PDA patients reported in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(23 citation statements)
references
References 17 publications
0
16
0
5
Order By: Relevance
“…For the minority of tumours that have been identified in the last two decades as being potentially sensitive to chemotherapy (van der Gaast et al, 1990;Pavlidis et al, 1992;Abbruzzese et al, 1995;Lenzi et al, 1997;Greco and Hainsworth, 2001b), the diagnostic procedures will delay these patients from receiving effective treatment.…”
mentioning
confidence: 99%
“…For the minority of tumours that have been identified in the last two decades as being potentially sensitive to chemotherapy (van der Gaast et al, 1990;Pavlidis et al, 1992;Abbruzzese et al, 1995;Lenzi et al, 1997;Greco and Hainsworth, 2001b), the diagnostic procedures will delay these patients from receiving effective treatment.…”
mentioning
confidence: 99%
“…These include: (i) peritoneal carcinomatosis or malignant ascites in women, particularly with serous cancers where ovarian cancer protocols are often effective, (ii) women with axillary lymph node metastases where treatment for occult breast carcinoma has been shown to be effective, (iii) male patients with osteoblastic bone metastases where empiric hormonal manipulation for metastatic prostate cancer would seem worthwhile, (iv) young males with undifferentiated carcinomas, involving retroperitoneal mediastinal lymph nodes where empirical treatment for germ cell tumour may be appropriate, (v) patients who present with metastatic squamous cell carcinoma in high cervical nodes where radical treatment for head and neck cancer is usually undertaken (Lenzi et al, 1997).…”
mentioning
confidence: 99%
“…7) Similarly, Currow et al found that only 2 of 9 patients in whom β-HCG was elevated to more than 8 times the upper normal limit responded to platinum-based chemotherapy. 13) Although the number of patients was small in the present study, significant elevation of β-HCG (>10 mIU/ml; that is, more than 20 times the upper normal limit), might suggest a better response to platinum-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%